Review papersAllergy to selected cosmetic ingredients - Żukiewicz-Sobczak, Wioletta A.; Adamczuk, Piotr; Wróblewska, Paula; Zwoliński, Jacek; Chmielewska-Badora, Jolanta; Krasowska, Ewelina; Galińska, Elżbieta M.; Cholewa, Grażyna; Piątek, Jacek; Koźlik, Jacek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
In an era in which cosmetics are commonly used, their often prolonged contact with the human body should determine the safety of their use. Often cosmetics are the cause of many side effects, mainly hypersensitivity reactions. Common groups of cosmetic components responsible for side effects are fragrances, preservatives and dyes. This paper focuses on the most allergenic components.